1982
DOI: 10.7326/0003-4819-96-6-723
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Information in Renal Biopsies of Patients with Lupus Nephritis

Abstract: To evaluate the informational value of renal biopsy in nephritis of systemic lupus erythematosus, we selected the records of 30 patients who had a renal biopsy done and also had a known clinical outcome. Detailed case histories were prepared, and three distinct randomly chosen cases were given to 197 academic rheumatologists. The rheumatologists estimated the probability of future clinical events (worsened serum creatinine, worsened urine protein, renal death, and aggressive therapy) at 3 and 12 months after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1984
1984
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…This policy may introduce a bias which may weaken the association between a poor renal outcome and the renal pathology, but no false associations may be introduced. Furthermore, it has been shown that renal biopsy results failed to add prognostic information about the future course of treated lupus nephritis to clinical information already obtained (17). With this reservation in mind we have analysed the in¯uence of demographic, clinical and renal biopsy data on the development of CRI and ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…This policy may introduce a bias which may weaken the association between a poor renal outcome and the renal pathology, but no false associations may be introduced. Furthermore, it has been shown that renal biopsy results failed to add prognostic information about the future course of treated lupus nephritis to clinical information already obtained (17). With this reservation in mind we have analysed the in¯uence of demographic, clinical and renal biopsy data on the development of CRI and ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the activity and chronicitiy indexes are useful to distinguish between patients with high versus low risk to develop end-stage renal failure. In fact, in a study assessing the impact of renal biopsy in the prediction of outcome, prognosis and management of LN, Whiting-O' Keefe et al [17] presented a questionnaire with several cases of LN to 197 rheumatologists; the results showed that renal biopsy was useful to predict which of the patients received aggressive treatment in the first 3 months of therapy. For this reason, we investigated the extent of agreement in the ability to score the activity and chronicity indexes of LN among three experienced pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely for a number of reasons. Firstly, while clinicians with considerable experience specifically in the management of lupus nephritis are expert at predicting both short-term and long-term outcome without recourse to renal biopsy data [16], this may not be true for all physicians [90]. Secondly, performing a renal biopsy frequently galvanizes an appropriate decision on treatment.…”
Section: Renal Biopsymentioning
confidence: 99%